Correlations among PPARγ, DNMT1, and DNMT3B Expression Levels and Pancreatic Cancer. (8th August 2012) - Pazienza, Valerio; Tavano, Francesca; Benegiamo, Giorgia; Vinciguerra, Manlio; Burbaci, Francesca Paola; Copetti, Massimiliano; di Mola, Fabio Francesco; Andriulli, Angelo; di Sebastiano, Pierluigi
Abstract : Emerging evidence indicates that peroxisome proliferator-activated receptor γ (PPAR γ ) and DNA methyltransferases (DNMTs) play a role in carcinogenesis. In this study we aimed to evaluate the expression of PPAR γ, DNMT1, and DNMT3B and their correlation with clinical-pathological features in patients with pancreatic cancer (PC), and to define the effect of PPAR γ activation on DNMTs expression in PC cell lines. qRT-PCR analysis showed that DNMT3B expression was downregulated in tumors compared to normal tissues (P = 0.03 ), whereas PPAR γ and DNMT1 levels did not show significant alterations in PC patients. Expression levels between PPAR γ and DNMT1 and between DNMT1 and DNMT3B were highly correlated (P = 0.008 and P = 0.05 resp.). DNMT3B overexpression in tumor tissue was positively correlated with both lymph nodes spreading (P = 0.046 ) and resection margin status (P = 0.04 ), and a borderline association with perineural invasion (P = 0.06 ) was found. Furthermore, high levels of DNMT3B expression were significantly associated with a lower mortality in the whole population (HR = 0.485; 95%CI = 0.262 –0.895, P = 0.02 ) and in the subgroup of patients without perineural invasion (HR = 0.314 ; 95%CI = 0.130 –0.758; P = 0.01 ), while such association was not observed in patients with tumor invasion into perineural structures (P = 0.70 ). In conclusion, in vitro and in vivo PPAR γ and DNMTs appear interrelated in PC, and this interaction might influence cell phenotype and disease behavior.